2000
DOI: 10.2527/2000.78123155x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of models of acute and subacute acidosis on dry matter intake, ruminal fermentation, blood chemistry, and endocrine profiles of beef steers.

Abstract: Crossbred steers (n = 20; 316 +/- 4 kg BW), each fitted with a ruminal cannula, were used to evaluate the effects of acute acidosis (AA) and subacute acidosis (SA) on DMI, ruminal fermentation, blood chemistry, and endocrine profiles. Animals were blocked by BW and assigned to treatments including 1) intraruminal (via cannula) steam-flaked corn (3% of BW; AA); 2) intraruminal dry-rolled wheat:dry-rolled corn (50:50; 1.5% of BW; SA); 3) offering forage-adapted steers ad libitum access to a 50% concentrate diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
96
3
11

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(125 citation statements)
references
References 30 publications
15
96
3
11
Order By: Relevance
“…That is consistent with the results of other authors who recorded increased concentrations of plasma phosphorus in association with experimentally induced acidosis in sheep (Patra et al, 1993;Brown et al, 1999). In contrast, Brown et al (2000) detected decreased levels of serum phosphorus after experimentally induced acidosis in fattened cattle. Average values of plasma magnesium and both transaminases AST and ALT were in the reference range in samples of both collections, and no statistically significant differences between the compared parameters of samples of the two collections were detected.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…That is consistent with the results of other authors who recorded increased concentrations of plasma phosphorus in association with experimentally induced acidosis in sheep (Patra et al, 1993;Brown et al, 1999). In contrast, Brown et al (2000) detected decreased levels of serum phosphorus after experimentally induced acidosis in fattened cattle. Average values of plasma magnesium and both transaminases AST and ALT were in the reference range in samples of both collections, and no statistically significant differences between the compared parameters of samples of the two collections were detected.…”
Section: Discussionsupporting
confidence: 83%
“…Burrin and Britton (1986), who obtained similar results, suggested that a decrease in blood pH and bicarbonate concentrations during the later phase of subacute acidosis indicated depletion of compensatory mechanisms. Less marked changes in bicarbonate and base excess concentrations were recorded during experimentally induced subacute acidosis by intraruminal administration of processed grain (Brown et al, 2000). Harmon et al (1985) found out more marked changes in bicarbonate concentrations after a switch to a diet containing 70% of concentrates, whereas pH decrease was insignificant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These signs was observed when ruminal pH values are near or lower than 5.0. The time frames detected in our study corroborate with findings of several studies on experimentally induced ALRA in cattle, which reported that the onset of signs occurred between 9 and 72h after induction, depending on the protocol adopted (Ortolani 1995, Brown et al 2000, Momcilovic et al 2000, Thoefner et al 2004, Danscher et al 2009, Rodrigues 2009). …”
Section: Discussionsupporting
confidence: 81%